Water Hyacinth: Promoting Rural Entrepreneurship with Special Reference to Assam - Bora, Bhaskarjyoti; Baruah, Natasha; Sahariah, Bulbul (AMC Indian Journal of Entrepreneurship, 2019)
Water Hyacinth also known as 'pani-meteka' in Assam is a free-floating aquatic plant with broad, thick, glossy, and ovate leaves which may rise above the surface of water as much as 1 meter in height. It is one of the most productive plants on Earth as it yields more than 200 tons of dry matter per hectare per year. This aquatic plant is grown in abundance in the rivers and lakes of Assam. Earlier it was considered nothing but waste. Now people have realized its eco-friendly benefits that would promote rural entrepreneurship. The main objective of this paper was to highlight how Water Hyacinth can help in promoting rural entrepreneurship. The study was based on data from secondary sources.